Evaluating the Trade, Revenue and Welfare Implication of Plantation Crops under ASEAN–India FTA. Issue 2 (September 2019) - Jagdambe, Subhash; Mouzam, Shaikh Mohd
Abstract: This article examines the impact of ASEAN–India Free Trade Agreement on India's special products categories, namely, coffee, tea and pepper based on partial equilibrium model. The Software for Market Analysis and Restrictive Trade (SMART) model has been used to estimate the trade creation (TC) and trade diversion (TD) effect, revenue effect and welfare effect for the above-mentioned commodities. The results from the SMART simulation analysis indicate that the increase in trade for both the scenarios is mainly driven by TC rather than TD. Further, the study also assesses how the total trade effect is distributed across the major ASEAN countries for each commodity and found that Indonesia and Vietnam are the biggest gainers in terms of TC effect in both the scenarios. JEL Classification: F13, F15, Q1